Excited-state hydrogen atom abstraction initiates the photochemistry of β-2′-deoxycytidine - Szabla, Rafał (Royal Society of Chemistry, 2015)

(untitled) (Chem Sci)
Understanding the effects of ultraviolet radiation on nucleotides in solution is an important step towards a comprehensive description of the photochemistry of nucleic acids and their constituents. Apart from having implications for mutagenesis and DNA photoprotection mechanisms, the photochemistry of cytidines is a central element in UV-assisted syntheses of pyrimidine nucleotides under prebiotically plausible conditions. In this contribution, we present UV-irradiation experiments of β-2′-deoxycytidine in aqueous solution involving H–D exchange followed by NMR spectroscopic analysis of the photoproducts. We further elucidate the outcome of these experiments by means of high-level quantum chemical calculations. In particular, we show that prolonged UV-irradiation of cytidine may lead to H–C1′ hydrogen atom abstraction by the carbonyl oxygen atom of cytosine. This process may enable photoanomerisation and nucleobase loss, two previously unexplained photoreactions observed in pyrimidine nucleotides.